Evaluation of The Anticancer Activity of Hydroxyxanthones Against Human Liver Carcinoma Cell Line - Yehezkiel Steven Kurniawan; Nela Fatmasari; Jumina Jumina; Harno Dwi Pranowo; Eti Nurwening Sholikhah (Pandawa Institute, 2024)
Nowadays, cancer is one of the most fatal diseases in developed and developing countries. Therefore, it is an urgent need to find more effective anticancer drugs among the recent commercially available standard drugs. Xanthone derivatives have been researched as anticancer drugs due to their ease of synthesis and structure modification, as well as their excellent anticancer activity. In this work, the in vitro anticancer activity of hydroxyxanthones against the human liver carcinoma cell line (HepG2) was evaluated. Among the twenty-two hydroxyxanthones, 1,3,6,8-tetrahydroxyxanthone was found as the most active anticancer agent with an IC50 value of 9.18 μM, which was better than doxorubicin as the standard drug. From the molecular docking studies against topoisomeraseIIα and two c-KIT protein kinases, 1,3,6,8-tetrahydroxyxanthone yielded strong binding energy in a range of -25.48 to -30.42 kJ/mol. The 1,3,6,8-tetrahydroxyxanthone could bind on the active site of these protein receptors through hydrogen bonds with key amino acid residues (Glu640, Cys673, Gln767, Met769, Asp810, and Asp831), as well as nitrogen bases (Adenine12 and Guanine13), thus leading to the death of HepG2 cancer cells through the apoptosis mechanism.